the sum of first n terms of an AP is 3xsuare -2x ,find AP
Answers
Question:
If the sum of first n terms of an AP is
3n^2 - 2n , then find the AP.
Note:(1)
In an A.P. ,the nth term is given by ;
T(n) = S(n) - S(n-1)
Also,
The common difference is given by;
d = T(n) - T(n-1)
Note:(2)
The nth term of an AP is also given by;
T(n) = a + (n-1)d , where a is the first term and d is the common difference.
Also,
To form any sequence , we require at least three terms.
Here,
S(n) = 3n^2 - 2n
Thus ,
S(n-1) = 3(n-1)^2 - 2(n-1)
= 3(n^2 - 2n + 1) - 2(n-1)
= 3n^2 - 6n + 3 - 2n + 2
= 3n^2 - 8n + 5
Hence,
=> T(n) = S(n) - S(n-1)
=> T(n) = (3n^2 - 2n) - (3n^2 - 8n + 5)
=> T(n) = 3n^2 - 2n - 3n^2 + 8n - 5
=> T(n) = 6n - 5
Now;
1st term of the AP = T(1)
= 6•1 - 5
= 6 - 5
= 1
2nd term of the AP = T(2)
= 6•2 - 5
= 12 - 5
= 7
1st term of the AP = T(3)
= 6•3 - 5
= 18 - 5
= 13
Hence, the required AP is ;